Zimbabwe Economic Update, February 2016 : Changing Growth Patterns - World Bank (World Bank, Washington, DC, 2016)
Low export prices and high production costs are contributing to a persistent deficit in the external accounts. Despite narrowing somewhat in recent years, Zimbabwe’s current account deficit remains much larger than those of comparable countries in the region, and exports currently amount to just over half of imports. A decline in global prices for gold, platinum and other mineral commodities, coupled with unresolved supply-side constraints, has reduced the value of mining exports. Zimbabwe has also benefited from lower oil prices, but rising import volumes largely offset the impact on import values. Remittances gradually increased during 2010-2015 and are estimated to have reached almost 7 percent of Gross National Income (GNI) in 2015. The domestic financial sector is slowly recovering from a post-dollarization credit boom and interest rates remain elevated. The Central Bank has stabilized the financial sector, a recent growth of broad money looks robust and bank lending has become market-driven. But still only blue-chip borrowers are able to access financing at competitive rates. The authorities are taking measures to update Zimbabwe’s credit infrastructure, strengthen oversight and restore the regulatory framework. Zimbabwe is experiencing a deflationary trend in response to these macroeconomic imbalances. The multicurrency regime, adopted in 2009, limits monetary policy instruments available to the authorities but also provides a level of fiscal and economic restraint. As competitive pressures increased, the consumer price index fell -2.5 percent, year-on-years, at end-2015. Declining prices should help to restore competitiveness over time, but should be accompanied by efforts to raise productivity at all levels of the economy.